2012
DOI: 10.1371/journal.pone.0044325
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Individual and Neighborhood Socioeconomic Status on Cancer Survival Rates

Abstract: BackgroundThis population-based study investigated the relationship between individual and neighborhood socioeconomic status (SES) and mortality rates for major cancers in Taiwan.MethodsA population-based follow-up study was conducted with 20,488 cancer patients diagnosed in 2002. Each patient was traced to death or for 5 years. The individual income-related insurance payment amount was used as a proxy measure of individual SES for patients. Neighborhood SES was defined by income, and neighborhoods were groupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 43 publications
1
88
1
1
Order By: Relevance
“…Low area-level SES has been associated with increased risk of cancer mortality in a few prospective studies, 39,[43][44][45] although a systematic review found no association. 42 Among Black Americans in the ARIC, cancer mortality rates were 30% higher in the lowest tertile of census block SES compared to the highest (.9-1.8).…”
Section: Discussionmentioning
confidence: 99%
“…Low area-level SES has been associated with increased risk of cancer mortality in a few prospective studies, 39,[43][44][45] although a systematic review found no association. 42 Among Black Americans in the ARIC, cancer mortality rates were 30% higher in the lowest tertile of census block SES compared to the highest (.9-1.8).…”
Section: Discussionmentioning
confidence: 99%
“…Most research explored determinants of aggressiveness of EOL care in older cancer deaths, and the results require validation in younger cohorts. For elderly patients, old age has an impact on treatment decision making for many diseases [12,31]. Older cancer patients tend to receive less aggressive treatment [3][4][5]31].…”
Section: Discussionmentioning
confidence: 99%
“…Other determinants, such as male sex, metastatic disease, and additional comorbidities, agree with previous studies from cancer deaths in those aged 65 years and older. A great body of literature has addressed the relationship between SES and mortality [12][13][14][15][16][17][18][19]. Low SES influences treatment of patients' diseases in many ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of colorectal and head and neck cancer patients in Taiwan, those with low individual SES living in disadvantaged neighborhoods has the highest mortality, as did those with breast and lung cancer with low individual SES living in advantaged neighborhoods (Chang et al, 2012).…”
Section: Cancer-related Stress and Physiological Disruption (Figure 1mentioning
confidence: 99%